Extracción de Líneas a partir de Escaneos Láser integrando Transformada de Hough, Mínimos Cuadrados Totales y Seguimiento de Bordes Sucesivos - Berrio, Julie Stephany; Orozco Ordoñes, Samith Aron; Caicedo Bravo, Eduardo Francisco (Ingeniería, 2012)
This paper presents a lines segmentation method, based mainly on a robust line extraction algorithm called Hough transform to obtain the preliminary parameters of straight lines composed of a set of points provided by a 2D láser scanner such as those used in robot navigation systems. The lines parameters obtained by the Hough transform algorithm are fitted by the Total Least Squares (improving the precision), and the points associated with these parameters are again processed by a Successive Edge Following algorithm in order to obtain the Cartesian coordinates of the extreme points of the lines which describe the environment.